Factors influencing health-seeking behaviours and self-care practices among black-African Caribbean people living with type 2 diabetes: a community-focused qualitative study from Southwestern England - Shahina Pardhan; Raju Sapkota; Pamela Knight-Davidson; Justin Roberts (BMJ Open)
Background/objective To examine factors influencing health-seeking behaviours and self-care practices of diabetes, including the uptake and use of diabetic services among community-dwelling black African-Caribbean people living in the UK.Design Cross-sectional/qualitative.Setting Community (Southwestern England).Participants Nineteen individuals of African-Caribbean heritage, over the age of 50 years, diagnosed with type 2 diabetes.Methods Three focus group discussions (FGDs), each of which lasted for approximately 90 min, were held. These interviews were facilitated by a community-based health champion and a researcher of African-Caribbean heritage. Audio recordings were transcribed verbatim, coded in NVivo software, and analysed using an inductive thematic approach.Primary outcome measures FGD data.Results A total of nine culturally specific and non-specific (generic) themes were identified. Culturally specific themes included the normalisation of diabetes at the community level, which was more pronounced among men than women. Participants were found to be inclined to either substitute or complement diabetes medications with cultural herbal remedies. There was a lack of trust in medical centric advice received from healthcare practitioners. Participants also expressed that healthcare practitioners do not always listen to or understand their needs and reported that there was a lack of culturally appropriate diabetes education and training programmes for their community members. Generic themes included difficulties and frustrations in getting doctor’s appointments, self-indiscipline and poor motivation for engaging in physical exercise and healthy eating.Conclusion Several cultural/community-related factors influence health-seeking behaviours and self-care practices of diabetes in African-Caribbean people living in the UK, often affecting men and women differently, alongside more general individual and healthcare system-related barriers. Addressing these factors is imperative in designing a culturally and demographically tailored diabetes education programme for these people.